Element bioaccumulation in lichens transplanted along two roads: The source and integration time of elements. (April 2019) - Zhao, Lili; Zhang, Chao; Jia, Shengju; Liu, Qingxue; Chen, Qingzhi; Li, Xing; Liu, Xiaodi; Wu, Qingfeng; Zhao, Liangcheng; Liu, Huajie
Highlights: Flavopunctelia soredica ( FS ) and Rhizoplaca chrysoleuca ( RC ) were transplanted. FS and RC are applicable biomonitors for atmospheric element deposition. FS and RC discriminate element sources and yield comparable results. FS and RC have shorter integration time for SO2 than for metals. Abstract: The biomonitoring of atmospheric element deposition via lichen transplantation is a powerful tool for assessing air quality in polluted areas devoid of native or expected lichens. In this paper, we explore how the elemental compositions in lichens respond to road emissions and compared the lichen responses under high air pollution conditions. Two foliose lichens, Flavopunctelia soredica ( FS ) and Rhizoplaca chrysoleuca ( RC ), were transplanted along two roads in a highly polluted area of Hebei, China. FS and RC were exposed to the road emissions for 3, 6, 9 and 12 months, and 25 elements (Al, Ba, Ca, Cd, Co, Cs, Cu, Fe, K, La, Mg, Mn, Na, Ni, Pb, Rb, S, Sb, Sm, Sr, Tb, Th, Ti, V, and Zn) were measured using an inductively coupled plasma mass spectrometer (ICP-MS). The pre-exposure and post-exposure results were higher in RC for 6 metals (Ca, Cd, Pb, La, Sm, and Tb), were higher in FS for 13 elements (Al, Ba, Co, Cu, Fe, K, Mg, Mn, Ni, Rb, S, V, and Zn), but were not significantly different between FS and RC for 3 metals (Cs, Sr, and Th), indicating that the element concentrations are specific to the element and lichen species. The results also showed a certain degree of air pollution at the initial site and severe air pollution at the exposure sites. During the exposure period, FS and RC exhibited roughly similar spatio-temporal patterns in element concentrations, with significant increases observed in relation to the distance to the road and exposure time. This result suggests that FS and RC are applicable as bioaccumulators and present good comparability. The release of SO2 in the winter heating period elevated the lichen S concentrations, for which the lichens have an integration time of <3 months, whereas the road emissions accelerated the accumulation of metals, for which the lichens have an integration time of >3 months.